Exosomes of A549 Cells Induced Migration, Invasion, and EMT of BEAS-2B Cells Related to let-7c-5p and miR-181b-5p - Liu, Yun; Su, Chao-Yue; Yan, Yan-Yan; Wang, Jian; Li, Jia-Jun; Fu, Ji-Jun; Wang, Yu-Qing; Zhang, Jian-Ye (Frontiers in Endocrinology, 2022)
As carriers containing abundant biological information, exosomes could deliver the property of donor cells to recipient cells. Emerging studies have shown that tumor cells could secrete a mass of exosomes into the microenvironment to regulate bystander cells. However, the underlying mechanisms of such a phenomenon remain largely unexplored. In this research, we purified and identified the exosomes of A549 cells and found that A549-cell-derived exosomes promoted BEAS-2B cells migration, invasion, and epithelial–mesenchymal transition (EMT). Importantly, we observed that let-7c-5p and miR-181b-5p were attenuated in A549-cell-derived exosomes compared to BEAS-2B-cell-derived exosomes. The analysis of miRNA expression level in BEAS-2B cells indicated that incubation with A549-cell-derived exosomes reduced the expression levels of let-7c-5p and miR-181b-5p. In transient transfections assay, we found that downregulation of let-7c-5p and miR-181b-5p simultaneously showed stronger promotion of BEAS-2B cells migration and invasion than individually. Moreover, exosomes secreted from A549 cells with upregulated expression of let-7c-5p and miR-181b-5p significantly reduce their regulatory effect on BEAS-2B cells. Bioinformatics analyses revealed that let-7c-5p and miR-181b-5p inhibit the EMT process mainly by regulating focal adhesion and mitogen-activated protein kinase (MAPK) signaling pathway. Thus, our data demonstrated that A549-cell-derived exosomal let-7c-5p and miR-181b-5p could induce migration, invasion, and EMT in BEAS-2B cells, which might be regulated through focal adhesion and MAPK signaling pathway. The expression level of let-7c-5p and miR-181b-5p may show great significance for the early diagnosis of lung cancer.